Adaptasi Mahasiswa Pendidikan Sosiologi dalam Pelaksanaan Praktik Pengalaman Lapangan Pasca Perkuliahan Daring - Hipe Helisa; Reno Fernandes (Universitas Negeri Padang, 2022)
This study aims to analyze student adaptation in implementing PPLK after online study for PPLK sociology education UNP students 2018 for the July-December 2021 period. This study was studied using structural functional theory by Talcott Parsons with the AGIL scheme. Functional Structural theory is a theory that views that all elements in society have their respective functions if one element does not function properly then problems will occur, so in this case the researcher sees that PPLK students are one of the elements in their society. must carry out its function properly even though there are obstacles. This research uses a qualitative approach with the type of case study research. Informant selection technique using Non Probability Sampling with Incidental Sampling technique, non-Probability Sampling is a sampling technique that does not provide equal opportunities for each sample element. There were 18 informants in this study, namely 10 students, 5 lecturers, 3 teachers, data collection was done by interview, observation, and documentation. The data analysis technique uses the Interactive model of Miles and Huberman (1992) which is divided into three activity flows, namely data reduction, data presentation, and data verification. The results of this study were adaptations made by students: 1. Preparing before teaching. 2. Prepare mentally. 3. Learn independently. 4. Self-motivated. 5. Adaptation to the school environment.